2018
DOI: 10.1007/s00330-018-5661-2
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance enterography, small bowel ultrasound and colonoscopy to diagnose and stage Crohn’s disease: patient acceptability and perceived burden

Abstract: • MRE and US are rated as acceptable by most patients and superior to colonoscopy. • MRE generates significantly greater burden and longer recovery times than US, particularly in younger patients and those with high levels of emotional distress. • Most patients prefer the experience of undergoing US than MRE; however, patients rate test accuracy as more importance than scan burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 26 publications
2
50
0
Order By: Relevance
“…The risk of low-dose radiation exposure is a concern for our growing population of young patients with IBD [24]. Miles et al [25], on behalf of the METRIC study, reports that younger patients and those with more emotional distress reported significantly increased burden and longer recovery times for MRE compared with US. This limits the available imaging modalities for patients younger than 9 years of age to CT or small bowel follow-through, which are not desirable due to the exposure to ionizing radiation [26].…”
Section: Resultsmentioning
confidence: 99%
“…The risk of low-dose radiation exposure is a concern for our growing population of young patients with IBD [24]. Miles et al [25], on behalf of the METRIC study, reports that younger patients and those with more emotional distress reported significantly increased burden and longer recovery times for MRE compared with US. This limits the available imaging modalities for patients younger than 9 years of age to CT or small bowel follow-through, which are not desirable due to the exposure to ionizing radiation [26].…”
Section: Resultsmentioning
confidence: 99%
“…The questionnaire combines a series of individual items into three main domains: satisfaction, worry and discomfort. The MRE questionnaire included 31 items (7, 6 and 18 in satisfaction, worry and discomfort domains, respectively) and the US questionnaire included 28 items (7, 6 and 15 in satisfaction, worry and discomfort domains, respectively), 60 additionally including an item relating to the abdominal pressure of the probe.…”
Section: Scan Burden For Magnetic Resonance Imaging and Ultrasonographymentioning
confidence: 99%
“…Scores for each item were reverse scored, totalled and averaged so that higher scores equated to higher burden. 60…”
Section: Scan Burden For Magnetic Resonance Imaging and Ultrasonographymentioning
confidence: 99%
“…This goal is then evaluated frequently to monitor progress and the treatment plan adjusted if the target is not achieved. Cross-sectional imaging may have a crucial role in this monitoring strategy as it is non-invasive with a lower complication rate then invasive colonoscopy, providing greater patient comfort and safety [41]. To achieve this, we must embed cross-sectional imaging into large clinical trials, so we can truly establish its added value, not only in monitoring disease response (for example as an endpoint in clinical trials of novel therapies), but also predicting longer term outcomes.…”
Section: Next Steps (Near Future)mentioning
confidence: 99%